Who do we trust on climate change, and why? - Sarah MacInnes; Matthew J. Hornsey; Christian Bretter; Samuel Pearson; Kelly S. Fielding; David Bersoff (Global Environmental Change, 2026)

Carcass use by mesoscavengers varied across modified landscapes in the absence of top carnivores - Matthew W. Fielding; Luke A. Yates; Jessie C. Buettel; Dejan Stojanovic; Barry W. Brook (Oecologia, 2025)
The decomposition of carrion is crucial to the functioning and nutrient cycling of ecosystems, and many species use this high-quality resource. However, the availability and reliability of carrion differs across environments. Modified landscapes, such as farms and roads, often produce a high density of carcasses, with disproportionate benefits for generalist mesoscavengers that can tolerate, or are attracted to, human presence. In this study, we placed carcasses strategically across two large islands in southern Australia and used camera traps to investigate how different scavengers locate and use carrion in forested, farmland and roadside habitats. Forest ravens, an avian generalist, were the dominant scavengers across all three habitat types but were three times more likely to discover carcasses deployed in modified landscapes. Raptors were twice as likely to discover and use carcasses in farmland habitats, indicating enhanced scavenging opportunities in these areas. The discovery rate and use of carcasses by feral cats did not differ between habitat types. In this setting, differences in carrion use between diurnal and nocturnal scavengers are potentially due to the absence of top mammalian carnivores (Tasmanian devils and quolls). Diurnal scavengers, such as forest ravens and raptors, followed expected habitat preferences, albeit with greater access to carrion due to increased persistence. However, feral cats demonstrated no preference for carcasses across habitats, likely due to the reduced landscape of fear. Overall, our study underscores the important role of native mammalian carnivores in structuring scavenger communities and further validates the value of trophic rewilding to restore key ecological functions.

Exploring Biases of the Healthy Eating Index and Alternative Healthy Eating Index When Scoring Low-Carbohydrate and Low-Fat Diets - Michelle E. Hauser; Jennifer C. Hartle; Matthew J. Landry; Priya Fielding-Singh; Cynthia W. Shih; FeiFei Qin; Joseph Rigdon; Christopher D. Gardner (Journal of the Academy of Nutrition and Dietetics, 2024)

Social interactions of dairy cows and their association with milk yield and somatic cell count - Helen R. Fielding; Matthew J. Silk; Trevelyan J. McKinley; Richard J. Delahay; Jared K. Wilson-Aggarwal; Laetitia Gauvin; Laura Ozella; Ciro Cattuto; Robbie A. McDonald (Applied Animal Behaviour Science, 2024)

Limited spatial co-occurrence of wildfire and prescribed burning on moorlands in Scotland - Debbie Fielding; Scott Newey; Robin J. Pakeman; Dave Miller; Zisis Gagkas; Keith Matthews; Stuart W. Smith (Biological Conservation, 2024)

Investigating how economic and national identity loss messages impact climate change policy support - Anna Klas; Edward J. R. Clarke; Kelly Fielding; Matthew Mackay; Susanne Lohmann; Mathew Ling (Climatic Change, 2022)

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

A framework for modelling soil structure dynamics induced by biological activity - Katharina Meurer; Jennie Barron; Claire Chenu; Elsa Coucheney; Matthew Fielding; Paul Hallett; Anke M. Herrmann; Thomas Keller; John Koestel; Mats Larsbo; Elisabet Lewan; Dani Or; et al. (Global Change Biology, 2020)
Soil degradation is a worsening global phenomenon driven by socio‐economic pressures, poor land management practices and climate change. A deterioration of soil structure at timescales ranging from seconds to centuries is implicated in most forms of soil degradation including the depletion of nutrients and organic matter, erosion and compaction. New soil–crop models that could account for soil structure dynamics at decadal to centennial timescales would provide insights into the relative importance of the various underlying physical (e.g. tillage, traffic compaction, swell/shrink and freeze/thaw) and biological (e.g. plant root growth, soil microbial and faunal activity) mechanisms, their impacts on soil hydrological processes and plant growth, as well as the relevant timescales of soil degradation and recovery. However, the development of such a model remains a challenge due to the enormous complexity of the interactions in the soil–plant system. In this paper, we focus on the impacts of biological processes on soil structure dynamics, especially the growth of plant roots and the activity of soil fauna and microorganisms. We first define what we mean by soil structure and then review current understanding of how these biological agents impact soil structure. We then develop a new framework for modelling soil structure dynamics, which is designed to be compatible with soil–crop models that operate at the soil profile scale and for long temporal scales (i.e. decades, centuries). We illustrate the modelling concept with a case study on the role of root growth and earthworm bioturbation in restoring the structure of a severely compacted soil.

Using ingroup messengers and ingroup values to promote climate change policy - Kelly S. Fielding; Matthew J. Hornsey; Ha Anh Thai; Li Li Toh (Climatic Change, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

The anatomy of population change in a black grouse population 1992–2008 - Matthew Geary; Alan H. Fielding; Stuart J. Marsden (Oecologia, 2012)

Analysing Extinction Risk in Parrots using Decision Trees - Martin J. Jones; Alan Fielding; Matthew Sullivan (Biodiversity and Conservation, 2006)

A Comparison of Predictive Methods in Extinction Risk Studies: Contrasts and Decision Trees - Matthew S. Sullivan; Martin J. Jones; David C. Lee; Stuart J. Marsden; Alan H. Fielding; Emily V. Young (Biodiversity and Conservation, 2006)